Ethics in a crowded world : globalisation, human movement and professional ethics - Harris, Vandra (Emerald Publishing Limited, 2019)
The twenty-first century has thus far been characterised by a persistent amplification of diverse and interconnected global flows, as well as various attempts to control, harness and channel these flows for individual and collective benefits. Whether we resist, appropriate, or simply observe those forces, for most of us they have meant significant change and adaptation.Conceiving crowdedness broadly, the work in this volume engages with increased exposure to the lives and realities of both proximate and distant others, facilitated by the perpetual motion of globalisation. The chapters approach crowdedness from a range of perspectives. These include a consideration of the expectations of migrating health professionals and the responsibilities of host governments, and humanitarian professionals' perspectives on whether their sector can genuinely localise. Two chapters consider research ethics in development and humanitarian practice respectively, and the final two propose a role for virtue ethics in addressing identity politics and employee motivation. Together these papers demonstrate the broad impacts of globalisation, turning to ethics to inform response and engagement now and in the unpredictable future.
Keywords: Globalization.; Business ethics.; Business & Economics -- General.; Economics, finance, business & management.; elektronické knihy; electronic books